Cardia function-preserving surgery and anti-reflux anastomotic method after proximal gastrectomy for gastric cancer: Current status and future perspectives - Li, Li; Liu, Zheng-hui; Cai, Xu-fan; Jiang, Qi-tao; Mou, Yi-ping; Wang, Yuan-Yu (Frontiers in Oncology, 2022)
The incidence and mortality of gastric cancer ranked 5th and 3rd worldwide, respectively, in 2018, and the incidence of gastroesophageal junction adenocarcinoma increased over the past 40 years. Radical resection and lymph node dissection is the preferred treatment for gastric cancer. Proximal gastrectomy or total gastrectomy is usually performed for gastroesophageal junction adenocarcinoma and upper gastric cancer. Owing to the resection of the cardia structures, the incidence of reflux esophagitis increases significantly after proximal gastrectomy and total gastrectomy, resulting in poor postoperative quality of life. To reduce the incidence of reflux esophagitis and improve patients’ postoperative quality of life, various methods to preserve the function of the cardia or to perform anti-reflux reconstruction have emerged. In this manuscript, we systematically introduced the advantages and problems of various anti-reflux anastomotic method after proximal gastrectomy, and cardia-preserving gastrectomy including endoscopic resection (ER), local gastrectomy by gastroscopy combined with laparoscopy, segmental gastrectomy, subtotal gastrectomy, and cardia-preserving radical gastrectomy. Cardia-preserving radical gastrectomy has the advantage of more thorough lymph node dissection and wider indications than those for subtotal gastrectomy. However, the clinical efficacy of cardia-preserving radical gastrectomy requires verification in prospective and controlled clinical trials. Cardia-preserving radical gastrectomy is a promising approach as one of the more reasonable anti-reflux surgeries.